An Implementation of Electronic Medical Records Reviewed from the Legal Aspects of Electronic Medical Records Security in Hospitals at Madiun City Area - Ardianingrum, Al Wafi Rahmaputri; Qurnia, Fadillah Yusuf (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
In the health sector in medical facilities, trying to switch from manual medical records to electronic medical records. In 7 Hospitals in Madiun City Electronic Medical Records have been implemented in 5 Hospitals and 2 Hospitals have not implemented Electronic Medical Records. The purpose of this study is to Know the Legal Aspects of EMR privacy data security, Knowing the Policy, Confidentiality, Integrity, Availability of Electronic Medical Records (EMR) in Hospitals in the Madiun City Region. This study uses a Qualitative Descriptive method. The subjects in this study were 9 people, namely 4 RM officers, 4 IT officers, 1 legal officer. The object in this study is the Implementation of Electronic Medical Records in 4 Hospitals in the Madiun City Region. The results of this study are There is no specific regulatory policy related to EMR available in all hospitals in the Madiun City Region. Confidentiality in 4 Hospitals is already on the access rights and users to each PPA. Data accuracy in patient data input on Integrity in 4 Hospitals. Availability of 4 Hospitals in EMR data requests and exchangebridging. The conclusions of this study have not been fully implemented, as all hospitals still do not have specific policies regarding RME. The recommendation from this study is that hospitals should create specific regulations or Standard Operating Procedures regarding changes to RME.